Strategi Guru dalam Menghadapi Siswa yang Lambat dalam Menangkap Pelajaran di Sekolah Dasar - Ribi Gulindari; Ari Suriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Basic education is a crucial stage in human resource development; however, not all students can follow the learning process at the same pace. Slow learners require special approaches to optimally understand the material. This study uses a descriptive qualitative method to examine teachers’ strategies in addressing slow learners in elementary schools. The findings indicate that curriculum modification, the use of engaging learning media, individualized approaches, collaboration with parents and schools, as well as inclusive and flexible classroom management are effective steps to support the success of slow learners. These approaches are expected to create an inclusive and equitable learning environment while enhancing student motivation and learning outcomes.